THE INFLUENCE OF AGILE LEADERSHIP ON TEAM PERFORMANCE ACROSS INDUSTRIES: SYSTEMATIC LITERATURE REVIEW - Purnomo, Santoso; Della Nur Rahmawati, Widya; Novana, Sonya; Althafiansyah Rosyidin, Gamma; Prayoga, Andhika; Tirta Raharja, Mulya; Kus Aprila Manto, Widia; Nisa, Khairun; Dharmawan Buchdadi, Agung (Penerbit Lafadz Jaya, 2025)
The rapid digital transformation requires organizations to be more adaptive, innovative, and able to deal with uncertainty. In this case, Agile Leadership is an important approach that supports business sustainability, improves organizational performance, and strengthens collaboration and continuous learning within teams. This study uses a Systematic Literature Review (SLR) to identify trends, theoretical frameworks, and research gaps related to the influence of Agile Leadership on team performance in various sectors. The results of the review show that agile leadership plays a role in building an adaptive organizational culture, strengthening communication, and encouraging innovation as the main factors in improving team performance in the era of digital transformation. This research confirms that the effectiveness of Agile Leadership is highly dependent on the organizational context, such as industry characteristics, work culture, and level of digital capabilities. A collaborative and fast-changing work environment can amplify the impact of agile leadership on team performance, while hierarchical structures and low digital capabilities hinder its implementation. Theoretically, the relationship between Agile Leadership and team performance is explained through the perspective of Dynamic Capabilities, Resource-Based View, and the principles of servant and inclusive leadership. The study concludes that Agile Leadership is a key factor in increasing organizational resilience and ensuring the relevance of companies in the complex and uncertain era of VUCA.